Comparative investigation on the Biological, Anatomical, Physical and Chemical Characteristics of reeds from Hooralazim and talab Anzali - Hossein Familian (Regional Information Center for Science and Technology (RICeST), 1997)
In this investigation, Biological, Anatomical, Physical and Chemical Characteristics of the Phragmites australis Var australis (Cav) Trin. Where  investigated in nine plots, at the Hooralazim in southern Iran and talab Anzali in northern of Iran. investigation of biological characteristics indicated that the mean culm diameter the culm pith diameter and internod length of reeds in the north is more than south. The average biological characteristics of P. australis is: culm length, 5.17 mm.; culm diameter, 13.99 mm. culm pith diameter 10.98 mm.; culm wall-thickness, 1.33mm.; Number of nods, 31 and internod length, 10.22 cm. Investigation of  Physical characteristics indicated that, density, shrinkage and swelling, in samplaes from south is significantly higher than samples from north. The investigation of chemical  characteristics indicated that, there is not significant difference between chemical  characteristics.